Female Subjects Oppressions in George R. R. Martin's A Song of Ice and Fire: A Game of Thrones - Wardani, L Dyah Purwita; Pratiwi, Adinia Arum; Supiastutik, Supiastutik (Universitas Negeri Gorontalo, 2022)
Female subjects' oppressions are a significant aspect of the novel entitled A Game of Thrones, published in 1996 by George R. R. Martin. This article aims to discover the discourse of female subjects' oppressions and the critical position of the author. The theory of representation by Stuart Hall and the discursive approach by Michel Foucault are used in this research. The contextual background and the narrations in the novel are collaborated in the analysis process to find the discourse of female subjects' oppressions and the critical position of the author. This research proves that this novel represents the oppression of female subjects in the form of marginalization, powerlessness, violence, and exploitation. Through the narration in the novel and some interviews, Martin, as the author, resists women's oppression.